750 Psychosocial risks in trade union representatives. (24th April 2018) - Ronsmans, S; Godderis, L
Abstract : Introduction: Quantitative studies reveal that trade union representatives are dealing with a number of specific psychosocial risk factors. The existing literature leaves many questions unanswered on the underlying reasons for these psychosocial risks and on difficulties in addressing them. A qualitative research could offer an opportunity to tackle this knowledge gap and to provide deeper understanding of this subject. Methods: Eight semi-structured in-depth interviews were conducted with trade union representatives from the 2 largest Belgian unions: ACV ( Confederation of Christian Trade Unions ) and ABVV ( General Federation of Belgian Labour ). A purposeful sample of participants was recruited from a wide range of sectors and types of work organisation. Template analysis was used to examine their unique job demands and job resources. Results: Using the job demands-resources model as a conceptual framework it was possible to map the unique psychosocial risk factors experienced by trade union representatives. Quantitative, qualitative and emotional overload, role conflict, role ambiguity and a conflictual relationship with their employers were found to be the major job demands. Social support from the workers, other representatives and the trade union were found to be the most important job resources, as well as having the knowledge and skills, experiencing success and having strong trade union beliefs. The findings of this study also suggest that workplace restructuring could profoundly impact the job demands and job resources experienced by trade union representatives. Conclusions: A rich and complex account of the experiences of the participants could be created. In general the results fit the existing literature but they add a deeper understanding of how and why trade union representatives are experiencing certain job demands and job resources. The study resulted in a wide range of propositions to improve the prevention of psychosocial risks in trade union representatives.